2016
DOI: 10.7456/1060ase/029
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Relation Between Organizational Learning Culture and Customer Satisfaction Using Job Satisfaction’s Mediating Variable in Insurance Industry

Abstract: The number of carried out activities in the academic field with the subject of organizational learning culture, customer satisfaction and job satisfaction has not been limited in Iran but in the meantime, distinction between different types of organizational learning has been neglected while on the other hand, addressing the issues of customer satisfaction and job satisfaction in the organizations such as insurances are considered as a necessity. Thus, this research tries to review the effect of organizational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
2
0
3
Order By: Relevance
“…Likewise, Johnson and McIntye (1998) mentioned that there are certain elements of culture (i.e., sharing, involvement and empowerment) that lead to employee satisfaction. Moreover, the relationship between the organizational learning culture and customer satisfaction where job satisfaction is researched as a mediating variable (Desa & Ding, 2016;Maleki, 2016). Likewise, Chang and Lee (2007) conducted research on a Taiwanese insurance company and concluded that employee satisfaction gets positively influenced by organizational learning culture.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Likewise, Johnson and McIntye (1998) mentioned that there are certain elements of culture (i.e., sharing, involvement and empowerment) that lead to employee satisfaction. Moreover, the relationship between the organizational learning culture and customer satisfaction where job satisfaction is researched as a mediating variable (Desa & Ding, 2016;Maleki, 2016). Likewise, Chang and Lee (2007) conducted research on a Taiwanese insurance company and concluded that employee satisfaction gets positively influenced by organizational learning culture.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Job satisfaction is a form of emotional and attitudinal response from employees towards their job [15]. Employees could sense of personal satisfaction regarding the dimensions of their; the type of work, the success rate, career improvement, enhancing ability and experiences, interaction with supervisor and co-workers, and the rewards.…”
Section: B Job Satisfactionmentioning
confidence: 99%
“…Kepuasan kerja dijelaskan oleh Maleki (2016) adalah sebagai suatu bentuk respon emosional dan perilaku karyawan ketika mereka mengevaluasi beragam dimensi yang terkandung dalam pekerjaannya. Dimensi tersebut bisa mencakup jenis pekerjaan, pengembangan karier, interaksi dengan atasan dan rekan kerja, serta kompensasi yang diterima.…”
Section: Pendahuluanunclassified